Smart Cities - Soldán, Michal (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2015)
Tato bakalářská práce se zabývá obecným úvodem do dílčích projektů, které jsou důležité pro realizaci chytrých měst i v nich používaných technologií. Podrobněji tato práce přibližuje projekty v různých zemích, hlavně však v Japonsku a na Havaji. Konkrétně shrnuje technologicky pokročilé energetické řešení a testovací projekty chytré sítě, které jsou základním kamenem pro budoucí chytrá města i efektivní využití elektomobilů. Práce také zmiňuje projekty chytrých měst v Evropě, kde je synchronizace vyvinutých technologií testována v praxi.

This bachelor's thesis deals with the general introduction into the projects that are needed for the realization of smart cities and technologies implemented in them. In further detail it concentrates more upon the projects that take place in different parts of the world, mainly in Japan and Hawaii. It deals, in particular, with technologically advanced energy solutions, smart grid testing projects which are essential for the smart city itself and implementation of electric vehicles into the grid. Also some of the European smart city projects are mentioned, where the developed technology is tested in real-life cooperation.
Smart Cities
Keywords: Chytrá města; chytrá síť; chytré domy; Havaj; Jokohama; Smart Cities; Smart Grid; Smart Homes; Hawaii; Yokohama